Improving Effective Hypertension Management in a Rural Primary Care Clinic Using American Heart Association Guidelines - Peters, Alexandra; Schaeffer, Ann (Journal of Practical Nurse Education and Practice, 2025)
Background: Hypertension affects nearly 50% of adult Americans and can lead to serious cardiovascular complications, including myocardial infarction, stroke, and death. The Centers for Disease Control [CDC] (n.d.) noted that hypertension costs $131 billion a year in healthcare visits, medications to treat high blood pressure, and loss of productivity due to premature death.Methods: The project consisted of four Plan-Do-Study-Act cycles that implemented two core interventions, with tests of change for each cycle driven by study of the data.Results: Repeating blood pressure measurements improved from 14% to 69% over eight weeks, with a z-score calculated regarding the aim with a pre- and post-implementation p < 0.0001. Hypertension screening was used with 84% of eligible participants, and patient engagement was used with 39%.Conclusions: This project improved hypertension screening and increased patient engagement. The interventions can be easily implemented in similar settings.